Aiding or enabling? Officer perspectives on harm reduction and support services in an open-air drug market - Wight, Hayley (Policing and society, 2024)
Police officers are stationed on the frontlines of open-air drug markets and regularly intervene in issues resulting from public drug consumption and overdoses. Police departments are increasingly being asked to adopt harm reduction approaches to deal with the health and safety consequences of drug use. As officer buy-in is essential to intervention success, it is important to assess officer attitudes towards their evolving duties. This study draws on over 400 hours of field observation data with transit officers deployed on an overdose rapid response programme in Philadelphia’s Kensington neighbourhood. Generally, officers were supportive of Narcan for overdose reversal, but some pointed out limitations to its use. Officers also identified how widespread availability of Narcan has changed the local overdose landscape and community response. Officers expressed mixed opinions towards ancillary support via food and clothing distribution by local organisations. They were more supportive of long-term treatment efforts though recognised the rarity of treatment initiation. Findings illuminate a tension in contemporary policing as officers rely less on law enforcement and adapt to harm reduction approaches in their daily work. Their perspectives identify potential benefits to enhanced training and understanding of harm reduction principles among police officers.